1999
DOI: 10.1042/bj3370329
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of pig mitochondrial 3-hydroxy-3-methylglutaryl-CoA synthase gene promoter: characterization of a peroxisome proliferator-responsive element

Abstract: Low expression of the mitochondrial 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) synthase gene during development correlates with an unusually low hepatic ketogenic capacity and lack of hyperketonaemia in piglets. Here we report the isolation and characterization of the 5´ end of the pig mitochondrial HMG-CoA synthase gene. The 581 bp region proximal to the transcription start site permits transcription of a reporter gene, confirming the function of the promoter. The pig mitochondrial HMG-CoA synthase promoter is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…We found that a PKA inhibitor did not influence SAA reduced perilipin promoter PPRE activity, suggesting that the effect of SAA reduced PPRE activity of perilipin is not from PKA. The porcine perilipin PPRE DNA sequence is an imperfect direct repeat‐1 element similar to what was shown previously (28). Therefore, we speculate that SAA‐induced lipolysis is due to a marked reduction in perilipin protein content, and enhanced lipase activity.…”
Section: Discussionsupporting
confidence: 71%
“…We found that a PKA inhibitor did not influence SAA reduced perilipin promoter PPRE activity, suggesting that the effect of SAA reduced PPRE activity of perilipin is not from PKA. The porcine perilipin PPRE DNA sequence is an imperfect direct repeat‐1 element similar to what was shown previously (28). Therefore, we speculate that SAA‐induced lipolysis is due to a marked reduction in perilipin protein content, and enhanced lipase activity.…”
Section: Discussionsupporting
confidence: 71%
“…However, the Sp1-binding site has also been reported to participate in Miz-1-mediated transactivation (38). The HMGCS2 transcription start site has been established by primer extension, S1 nuclease protection, and rapid amplification of cDNA ends experiments in rat (11), pig (41), and human (15) genes and does not contain a canonical Inr sequence. Mutation of critical elements in the HMGCS2 proximal promoter diminished its transcriptional activity and therefore hinders the study of Myc transrepression.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies using cell cultures have demonstrated that CLA acts as an agonist of the peroxisome proliferator activated receptor family (PPAR). PPARs are DNA binding transcription factors that bind the peroxisome proliferator repeat element (PPRE) (2, 3, 4) as a heterodimer with the retinoic acid receptor (RxR), which is activated by 9-cis-retinoic acid (vitamin A) (5, 6). The PPAR family is currently divided into three subgroups, α, β and γ. PPARβ is expressed throughout the body and is involved in embryo development (7, 8).…”
Section: Introductionmentioning
confidence: 99%